Complementary and Alternative Medicine Utilization among Pregnant Women Attending Antenatal Care Clinics in Tongaren Sub-County, Kenya: a Cross-sectional Survey - MARTHA MAKHAPILA; George Makalliwa; Samuel Mong’are (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background: In Kenya, Complementary and Alternative Medicine (CAM) has been used in almost every culture to manage intolerable symptoms of pregnancy since ancient times. However, studies in Kenya have focused on herbal medicine which is just one of CAM practices. In rural settings (such Tongaren Sub-County), no studies have ever evaluated the prevalence and determinants of CAM use during pregnancy including the common CAM modalities used, and so there is need to bridge these knowledge gaps. Purpose: This study aimed at determining the prevalence of CAM utilization and associated factors among pregnant women attending antenatal care clinics in Tongaren Sub-County, Bungoma County. Methods: A cross-sectional descriptive study design was employed in collecting data from 340 pregnant women attending antenatal clinics in Tongaren, Kenya. Quantitative data was collected through semi-structured questionnaires. Chi-square test was used to establish the associations between socio-demographic variables and CAM usage, and multiple logistic regressions were used to examine the relative effects of the various aspects of the variables which were significantly associated with CAM usage. Results: Among the 340 participants, 50.7% indicated using CAM modalities during pregnancy, indicating that CAM use prevalence in Tongaren is about 50%. 55.80% of CAM users concomitantly use CAM and conventional medicine. The high CAM use prevalence among participants was motivated by the preference of CAM over conventional medicine for certain illnesses (31.4%) and the perceived lack of response to conventional medicine (20.1%). It was noted that marital status, educational attainment of the spouse, employment status, occupation type, and household monthly income level are the major determinants of CAM usage. From the logistic regression analysis, the variables positively associated with CAM use among pregnant women were married status (Odds ratio (OR) = 2.341, p = 0.008), having a spouse with informal education (OR = 5.371, p < 0.001), self-employed status (OR = 0.415, p = 0.028), farming occupation (OR = 2.777, p = 0.206), and household monthly income higher than 35,000 Kshs (OR = 0.093, p = 0.012). Conclusions: Due to the widespread trust in the safety and efficacy of CAM, the utilization of CAM during pregnancy is common among women in Tongaren Sub-County, which is a rural setting, and therefore CAM can be regarded as the backbone of rural health care in Kenya.